The role of cyclooxygenase-derived oxidative stress in surgically induced lymphedema in a mouse tail model. (May 2013) - Chang, Ting-Chen; Uen, Yih-Huei; Chou, Cheng-Hung; Sheu, Joen-Rong; Chou, Duen-Suey
Abstract Context: Oxidative stress may contribute to lymphedema and subsequent tissue damage. However, the causal role of oxidative stress in lymphedema remains unclear. Objective: We attempted to detect and identify the free radicals formed in lymphedema fluid and assessed the protective mechanisms and effects of specific enzyme inhibitors and natural antioxidants. Materials and methods: To study the level of postsurgical oxidative stress with lymphedema in a mouse tail model, we used an electron spin resonance (ESR) method and an ascorbyl radical's ESR spectrum as an oxidative stress biomarker. The drug-treatment group received an i.p. injection with indomethacin (2 mg/kg), baicalein (15 mg/kg), MK-886 (3 mg/kg), zileuton (6.25 mg/kg), diphenyleneiodonium (DPI; 1 mg/kg), sulforaphane (30 mg/kg), oryzanol (30 mg/kg) or sesamol (30 mg/kg) once daily for 14 d from the day of operation. All animals were sacrificed on day 14. Results: Administration of indomethacin, sulforaphane, oryzanol and sesamol significantly suppressed both the tail volume (56.9%, 77.8%, 72.2% and 38.1% inhibition, respectively, p < 0.01) and ascorbyl radical signals (31.4%, 54.5%, 79.3% and 57.1% inhibition, respectively, p < 0.01), compared with the control mice. No significant differences were found between any of the baicalein, MK-886, or zileuton groups compared with the control. DPI suppressed the tail volume (25.9% inhibition, p < 0.01) but not the ascorbyl radical signals. Conclusion: This study showed that COX-derived oxidative stress plays a major role in the pathological mechanisms of surgically induced lymphedema. Indomethacin, sulforaphane, oryzanol and sesamol exhibit potent protective properties against surgically induced lymphedema.